2013
DOI: 10.1097/aud.0b013e31827ad76f
|View full text |Cite
|
Sign up to set email alerts
|

Using Personal Response Systems to Assess Speech Perception Within the Classroom

Abstract: PRS together with the CAPT provides a sensitive measure for in situ speech perception testing within the classroom. Vocabulary age has a large effect on a child's ability to perceive the speech signal. SFA leads to improved speech perception, when the speech signal has been degraded because of poor acoustics or background noise and has a particularly large effect for children with lower vocabulary ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Children had a practice run that consisted of 4 words to familiarize them with the process. Following Vickers’ speech test procedure [ 27 ], each child was assigned a hand-held infrared transmitter to record her or his response to each trial. Turning point software and a USB receiver were used to capture the children’s responses.…”
Section: Methodsmentioning
confidence: 99%
“…Children had a practice run that consisted of 4 words to familiarize them with the process. Following Vickers’ speech test procedure [ 27 ], each child was assigned a hand-held infrared transmitter to record her or his response to each trial. Turning point software and a USB receiver were used to capture the children’s responses.…”
Section: Methodsmentioning
confidence: 99%
“…Our aim was to ensure that people were operating at the same point on the psychometric function. We selected the 50% point on the speech identification psychometric because we wanted the majority of scores to fall above chance plus the critical difference for the CAPT (18% ( Vickers et al., 2013 )) and below 100% minus the critical difference, that is, 43% to 82%.…”
Section: Methodsmentioning
confidence: 99%
“…Excessive noise level, however, is the most significant contributor affecting speech perception (Sato & Bradley, 2008;Yang & Bradley, 2009). Many studies have shown the detrimental effect of noise on children's speech perception, reading and language comprehension, cognition, concentration, learning, and psychoeducational and psychosocial development (American Speech-Language-Hearing Association, 2005;Anderson, 2001;Crandell & Smaldino, 1995;Dockrell & Shield, 2006;Finitzo-Hieber & Tillman, 1978;Jamieson et al, 2004;Klatte, Lachmann, & Meis, 2010;Ronsse & Wang, 2010, 2013Shield et al, 2010;Vickers et al, 2013).…”
mentioning
confidence: 99%